Prevalence of White Spot Caries Lesions in Primary Teeth in Preschool Children: Systematic Review and Meta-analysis - Campos, Priscila H.; Gimenez, Thais; Rocha, Rafael S. [UNESP]; Caneppele, Taciana M. F. [UNESP]; Guaré, Renata O.; Lussi, Adrian; Bresciani, Eduardo [UNESP]; Diniz, Michele B. (Bentham Science Publishers, 2022)
Background: The first clinically detectable stage of caries lesion is a non-cavitated white spot lesion (WSL). The detection of early stages of caries lesions allows non-invasive management by fluoride usage, oral hygiene and diet control. There is a lack of information in the literature regarding the prevalence of these caries lesions in preschool children, which is important especially for public health strategies. Objective: The aim of this study was to conduct a systematic review with meta-analysis to verify the WSLs prevalence in primary teeth of preschool children. Methods: A literature search with MEDLINE/PubMed, Scopus, Web of Science, and Open Gray databases was conducted. Included studies fulfilled the eligibility criteria. Meta-analyses were performed using random effects model, for prevalence of pooled WSLs and subgroups analyses. Results: The search strategy identified 4922 potentially relevant articles, with final inclusion of 16 studies. The pooled prevalence of WSLs in primary teeth was 14.0% (95% CI: 8.0-24.0), without publication bias (p=0.2668). For subgroup analyses, an increase in WSLs prevalence for children of low-income economy (24.0%; 95% CI: 20.0-28.0), for age >31 months (22.0%; 95% CI: 12.0-37.0), for validated visual criteria assessment (20.0%; 95% CI: 11.0-33.0), and for tactile assessment with ball-ended probe (26.0%; 95% CI: 11-50.0) were detected. Conclusion: It is suggested that the prevalence of WSLs in primary teeth of preschool children increases in countries with low income economy, with age greater than 31 months or texture assessment with visual validated criteria or ball-ended probe. PROSPERO Registration: Protocol number #CDR42017078434.
Keywords: Dental caries; meta-analysis; preschool child; prevalence; primary teeth; white spot lesions